2022
DOI: 10.1039/d2gc01808j
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient catalytic transfer hydrogenolysis for the conversion of Kraft lignin into bio-oil over heteropoly acids

Abstract: Catalytic transfer hydrogenolysis (CTH) has emerged as a sustainable and carbon-neutral biorefinery due to the decrease in the carbon footprint and the high atom and energy efficiency. Herein, heteropoly acids...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The efficient liquefaction of lignin in isopropanol was related to the distinguished hydrogen donating ability of isopropanol. 34 Considering the possibility of industrial application, ethanol solution is probably the most suitable solvent due to its excellent liquefaction capacity and relatively lower price.…”
Section: Resultsmentioning
confidence: 99%
“…The efficient liquefaction of lignin in isopropanol was related to the distinguished hydrogen donating ability of isopropanol. 34 Considering the possibility of industrial application, ethanol solution is probably the most suitable solvent due to its excellent liquefaction capacity and relatively lower price.…”
Section: Resultsmentioning
confidence: 99%
“…Their FT-ICR-MS showed that the signal at m / z was over 500 and weakened after the hydrogenolysis of the Kraft lignin. 113 Song et al employed the Maldi-TOF technique to analyze oligomeric fractions from lignin alcoholysis (methanol) and indicated that the depolymerized products with molecular weight from m / z ca. 1100 to ca.…”
Section: Identification Of Oligomeric Productsmentioning
confidence: 99%
“…3 Molecular weight distribution (Maldi-TOF-MS) or the average molecular weight (GPC or FT-ICR-MS with the double bond equivalent value) for the products from various lignin depolymerization processes. 7,9,33,55,98,[109][110][111]113,114,[116][117][118][119][120][121][122][123][124] Industrial Chemistry & Materials Review parameters, such as T1 and T2 relaxation rates, carbon pulse offset effects, and multiplicity and magnitude of coupling constants. 129,130 Fig.…”
Section: Industrial Chemistry and Materials Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These acids are extensively utilized in the delignification of lignocellulosic pulp and as redox catalysts for the hydrogenolysis/hydrodeoxygenation (HDO) of lignin [29,30] . In the context of lignin hydrogenolysis, POMs have been used as cocatalysts with Pd/C to deter the condensation reaction [31,32] . However, the need to master the synthetic parameters remains imperative to fully leverage the potential of POMs and to design materials with synergetic capabilities.…”
Section: Introductionmentioning
confidence: 99%